Diseño de un plan de negocio de granja de salmonidos caso finca “Las Lagunas” (2020)
The document develops a business plan for the “LAS LAGUNAS” farm as a business alternative to implement on its grounds. The work includes the external and internal diagnosis of the industry environment. It was found that fish farming is a market that has been developing in the country for several years, but it is an underdeveloped market, the trout producers in the country produce exclusively for export, thus leaving unsatisfied national demand. According to the characterization of the farm, it was found that it has several competitive advantages over its competitors. The designed business plan states that the market must be entered with an aggressive penetration strategy in order to position the company as one of national main suppliers.